Dallas : Season 1-6 - Day, Robert; Principal, Victoria; Patrick Duffy; Larry Hagman; Barbara Bel Geddes; Linda Gray; Moore, Irving J. (USA Lorimar Television, 1978)
Popular evening 'soap-opera' style television drama. The show was set in Dallas and chronicled the exploits of wealthy Texas oil millionaires. Many of the plots revolved around shady business dealings and dysfunctional family dynamics.
The soapy, backstabbing machinations of Dallas oil magnate J.R. Ewing and his family.
David Jacobs
Language: English Subtitles: English
Keywords: Tv Series; Drama